Enhancing Students’ Understanding of Fiqh through the Jigsaw Learning Model at MAN 3 Padang Panjang - Hafizah Muchtia; Yahdi Dinul Haq (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students’ understanding of Fiqh at MAN 3 Padang Panjang through the implementation of the Jigsaw learning model. Fiqh, being a core subject in Islamic studies, requires students to not only memorize laws but also to understand their application in daily life. Traditional methods often emphasize rote learning, which may lead to passive engagement from students. The Jigsaw model, an active learning strategy that promotes collaboration and group work, is employed to foster deeper engagement, critical thinking, and mutual learning among students. The research was conducted in two cycles with 11th-grade students at MAN 3 Padang Panjang. In each cycle, students were divided into small groups, with each group member assigned a section of the Fiqh material to learn. After studying their sections, they were regrouped with other members from different groups to share their findings, allowing them to collectively piece together a complete understanding of the topic. Data were collected through observations, student surveys, and pre- and post-tests to measure changes in student engagement, understanding, and group collaboration skills. The results indicated that the Jigsaw model significantly improved students’ understanding of Fiqh. Students were more engaged in the learning process, demonstrated improved collaboration skills, and showed a better grasp of Fiqh concepts. The cooperative nature of the Jigsaw model allowed students to learn from one another, reinforcing their understanding and promoting a deeper connection to the material. This study concludes that the Jigsaw learning model is an effective method for enhancing students’ comprehension of Fiqh and fostering a more interactive, student-centered learning environment.